2002
DOI: 10.1007/s10350-004-6334-6
|View full text |Cite
|
Sign up to set email alerts
|

Adults in a High-Risk Area Are Unaware of the Importance of Colorectal Cancer

Abstract: Knowledge of colorectal cancer among the surveyed population was poor despite a relatively high incidence of the disease in Singapore. Public education regarding colorectal cancer is best done via newspapers and magazines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 8 publications
4
17
0
Order By: Relevance
“…Whitecollar men might have higher awareness of colorectal cancer and its screening and less of a financial issue than blue-collar men. Our results indicated that poor knowledge of colorectal cancer screening was a major barrier to improving the screening rate, which is supported by reports that poor knowledge of colorectal cancer screening is a prognostic factor of screening rates in Chinese communities in Singapore [16,17] . Public education about colorectal cancer, risk factors, and potential benefits from colorectal cancer screening should be performed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Whitecollar men might have higher awareness of colorectal cancer and its screening and less of a financial issue than blue-collar men. Our results indicated that poor knowledge of colorectal cancer screening was a major barrier to improving the screening rate, which is supported by reports that poor knowledge of colorectal cancer screening is a prognostic factor of screening rates in Chinese communities in Singapore [16,17] . Public education about colorectal cancer, risk factors, and potential benefits from colorectal cancer screening should be performed.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, 415 people refused the free colonoscopy [15] . Though poor knowledge about colorectal cancer, social factors and the test provider might have influenced compliance of colorectal cancer screening [16][17][18][19][20][21] , it is not clear why people are unwilling to attend the colorectal cancer screening program in China. To better understand why people are unwilling to attend the colorectal cancer screening program in China, we conducted this study to explore the barriers to conducting a colorectal cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, awareness of colorectal cancer and screening is low. [35][36][37][38] Our results suggest that much attention should be paid to the information given; it must appeal to men, people who are unmarried or divorced, and people with low socioeconomic status. It appeared that personal invitations by telephone did not importantly modify the effect of gender and variables reflecting the socially and economically deprived status suggesting that an increased social pressure on unmotivated invitees from the inviting center may not be more than moderately helpful.…”
Section: Discussionmentioning
confidence: 89%
“…In that study of Harmy et al (2011), 62.3% of the study participants did not know about Faecal Occult Blood Tests (FOBT) and 63.3% knew nothing about colonoscopy. Another study from Singapore showed a higher percentage of a lack of knowledge about colorectal cancer screening in which about 70% of the Chinese respondents had not heard of or knew anything about colonoscopy (Wong et al, 2002). A study from Hong Kong showed that colonoscopy was the most mentioned colorectal screening test (33%), followed by sigmoidoscopy (6.3%) and FOBT (5.9%) (Wong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%